FAKTOR DETERMINAN KAPASITAS VITAL PARU PEKERJA WANITA BAGIAN PEMUPUKAN - Trisnawati, Elly (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2015)
Nowadays, there are more women workers occupying various types of works, and it expands to the area of oil palm plantation. One of which is women workers who work at fertilization section in oil palm plantation. This condition is vulnerable for the women workers due to the dust exposure from urea fertilizer. There are some likely possible risk jobs encountered by the women workers such as pulmonary function impairment indicated by lung vital capacity. From pre observation, it was found out that there were 60% of women workers who committed to respiratory disorders. About 80% from the women workers did not use proctected mask during the process of fostering the plantation. As a result, the long term goal of conducting this research is to get accurate information on the determinant factor of lung vital capacity of women worker at fertilization section which can be grounded as basic recommendation for the arrangement of Occupational Health and Safety (OHS) at oil palm plantation.Based on the problem identification, this research was designed by employing quantitative method of research with cross-sectional design. The observed and analyzed variables were the characteristics, the description of lung vital capacity of women workers, and influential factors to the lung vital capacity. This research was conducted to 50 women workers at fertilization area in oil palm plantation, Kebun Gunung Emas Kalimantan Barat. The data were analyzed through 2 phases of analyses namely univariable analysis and bivariable analysis using chi square test and prevalence ratio (PR). The findings of the research revealed that the associated factors with the lung vital capacity of women workers on fertilization area were the dust exposure (p value = 0,000 ; r = -0,650**) while the age variable, years of service, and nutrional status were not related to the lung vital capacity of women workers on fertilization area. The unanalzyed variables resulted from the homogeneity data were the length of exposure, and the use of personal protective equipment (PPE). All women workers rarely used PPE with its length of exposure 4 hours per day. As a result, it is recommended to the management of the oil palm plantation to make a policy on the obligation of using PPE for women workers at fertilization area because the amount of dust exposure exhaled by the workers is the main factor. It is also expected that the company can promote a counselling for the workers to do fertilization safely.